Hymnen: Elektronische und konkrete musik - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2008)
Stockhausen Introduction to HYMNEN ( Archive No. 135 / 1 )( Colour film by Suzanne Stephens )Pre - concert introduction to HYMNEN ( ANTHEMS ) by Karlheinz Stockhausen at BarbicanHall, October 13th 2001, London. )